(untitled) (Research, Society and Development, 2020)
Oral health conditions of patients in intensive care units (ICU) is often very precarious. This study was conducted in the ICU to identify oral changes of this population. Material and Methods this was an exploratory, descriptive and cross-sectional study. The data collected included age, gender, oral hygiene condition, reasons for hospitalization, oral changes and management. Two trained dentists performed the clinical oral examinations using wooden spatulas and sterile gauze. 104 patients between 19 and 92 years of age (56.82 ± 18.23 years) were analyzed, comprising 26 women and 78 men. Most of the patients presented good hygiene. The most common reason for admission was traumatic severe brain injury. Fifty-nine patients (56.7%) had at least one oral lesion. Most frequent lesions were lip dryness (26.3%), traumatic ulcers (TU) (20.0%) and tongue coating (20.0%). According to our results, traumatic ulcers represent a challenge for physicians, the participation of a dentist and a dental hygienist would help to manage and prevent infections of these lesions, making a truly interdisciplinary team essential for the quick recovery of ICU patients.